Fluctuations in Direct Investment in Indonesia - Taufik, Mohamad (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2014)
This study aims to analyze the effect of interest rate, Gross Domestid Product (GDP) per capita, exchange rate Rupiah to U.S.$, net export, tax rate, tax incentives (tax allowances), and ease of service and licensing to FDI in Indonesia during the period 1985-2011. The analysis model used in this study is a multiple regression model of time series data so will know the factors affecting FDI in Indonesia during the period 1985-2011. The result shows that variable interest rate, GDP per capita, exchange rate Rupiah to U.S.$, tax rate, tax incentives (tax allowances), and ease of service and licensing have a significant effect on the entry of FDI in Indonesia, but the net export variable have not a significant effect on the entry FDI.